Pengaruh Mekanisme Good Corporate Governance dan Profitabilitas Terhadap Nilai Perusahaan Perbankan yang Terdaftar di BEI - Novitasari, Devi; Kusumowati, Dewi (University of Merdeka Malang, 2021)
This study aims to analyze the effect of good corporate governance and profitability simultaneously on firm value, to analyze the effect of good corporate governance on firm value, and to analyze the effect of profitability on the value of banking companies listed on the Indonesia Stock Exchange. The population in this study was because there were 43 issuers, the sampling technique used was a purposive sample, so that a sample of 17 banks was obtained during the period 2015-2019. The data analysis technique used multiple linear regression analysis, classical assumption test, F test, and t-test. Based on the results of the analysis, it shows that good corporate governance and profitability simultaneously affect the value of banking companies listed on the Indonesia Stock Exchange. Good corporate governance has a positive and significant effect on the value of banking companies listed on the Indonesia Stock Exchange. Profitability has a significant positive effect on the value of banking companies listed on the Indonesia Stock Exchange